Religion and Peace in the Middle East: Edited by Frank Kaufmann and Justine Watson; Council for the World’s Religions, 1988 (American Journal of Islam and Society, 1989)
This slim volume is based on the three papers presented at the Councilfor the World’s Religions (CWR) conference on “Interreligious Dialogue andPeace in the Middle East” held in Toledo, Spain in March 1988. The conferencewas intended to discuss the role of religion in the pursuit of peace in theMiddle East.The volume begins with a paper on “Religion and Politics: Dangers andPossibilities for Peace in the Middle East” by Rabbi David J. Goldberg.Goldberg argues that the on going Arab-Israeli conflict is essentially politicaland not religious in its origin, its cause, and in the perception of those mostintimately involved. Hence, the resolution of conflict could only come froma concerted effort to find an acceptable and mutually beneficial geo-politicalhrmula which seeks to accommodate the just demands and needs of both parties.Any attempt to seek a solution only in “apocalyptic terms” would undoubtedlylead to more conflicts and wars. Goldberg claims that religious differencesdid not originally loom large as a source of conflict in the Middle East.This may be true before 1967. But since the Israeli occupation of El-Quds,the religious dimension of the Arab-Israeli conflict has become equally, ifnot more, important than the political dimension. For Muslims throughoutthe world, the constant reminder that one of the three holiest places in theirreligious tradition is out of their reach cuts a deep psychological wound.Rabbi Goldberg believes that common to the three monotheistic faiths ofthe Middle East are “certain shared principles” that govern ethical behavior,recognize the rights of other people, and determine responsibilities ofgovernments. The logic of acknowledging and re-affirming these sharedprinciples may open new possibilities of conflict resolution and mutualunderstanding. Goldberg states: “As a Jew, therefore, I have no hesitationin asserting that the Palestinian right to self-determination is just as validas my insistence on Jewish self-determination.”Farhang Rajaee’s paper on “Religion and Politics in Islam: The IranianContext” is an important attempt to understand “the internal logic” of Islamwith regard to religion and politics or the relations between the secular andthe sacred. Rajaee argues that the aim of politics in Islam is identified withreligion. Seeing Islam as a systematic whole implies that “the distinctionand separation between various aspects of life make little sense.” Politics, ...